Pelatihan penyelenggara diklat bagi komunitas kerja guru di Kabupaten Lamongan - Rosdiana, Silvi Rosiva; Febriyanti, Rahma; Mahbubah, Khoiro; Rahmawati, Santi; Hamidah, Imroatul (Abdimas Siliwangi, 2024)
One of the demand of teacher performance assessment is that teacher must be active in improving his competence by participating in various kinds of training. However, this policy ultimately triggers teachers not to focus on improving their own quality, but only to focus on certificate quantities. Thus, it can be concluded that the increase in the number of certificates collected is not in line with the expected increase in competency. Given this problem, the Teacher Working Community (TWC) considers it necessary to improve the quality of teacher performance through training activities to become training providers. So in this case, the increase in the number of certificates collected by teachers will be proportional to the competencies they possess. The stages of implementing activities begin with socialization, followed by training, then mentoring and evaluation and the program sustainability stage. The result of holding this training was that the percentage of understanding of the participants was 72% which was categorized as Good. Apart from that, the response from the participants regarding the holding of this training was very good. The sustainability of this training program is to continue the training program for training organizers in other TWC clusters with a wider network scope.